2021
DOI: 10.1093/nar/gkab764
|View full text |Cite|
|
Sign up to set email alerts
|

Theoretical basis for stabilizing messenger RNA through secondary structure design

Abstract: RNA hydrolysis presents problems in manufacturing, long-term storage, world-wide delivery and in vivo stability of messenger RNA (mRNA)-based vaccines and therapeutics. A largely unexplored strategy to reduce mRNA hydrolysis is to redesign RNAs to form double-stranded regions, which are protected from in-line cleavage and enzymatic degradation, while coding for the same proteins. The amount of stabilization that this strategy can deliver and the most effective algorithmic approach to achieve stabilization rema… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 60 publications
1
62
0
Order By: Relevance
“…Kinetic models describing mRNA degradation have been developed based on firstorder kinetics at physiological pH ranges [21][22][23]. It was also shown that this mRNA degradation reaction follows the Arrhenius behavior [21,24].…”
Section: Mrna Vaccine Instability and Stability Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic models describing mRNA degradation have been developed based on firstorder kinetics at physiological pH ranges [21][22][23]. It was also shown that this mRNA degradation reaction follows the Arrhenius behavior [21,24].…”
Section: Mrna Vaccine Instability and Stability Modellingmentioning
confidence: 99%
“…However, the temperature reading from these monitoring devices can feed into computational degradation kinetic models. Therefore, modelling of mRNA degradation kinetics can be feasible [21][22][23][24][25] and with further investigation the impact of temperature exposure profiles on CQAs can be assessed [26][27][28]. Therefore, here solutions are conceptualised to quantify the impact of the distribution conditions, including temperature excursions, on the remaining shelf life and on the stability-related CQAs of these thermolabile mRNA vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…An illustrative example of how deviation to even one factor of the ones mentioned above can compromise mRNA integrity, arises from the rigorous study of SARS-CoV-2 mRNA vaccine stability: under strict “cold-chain” transport conditions a naked RNA molecule encoding the virus’s spike has a calculated half-life of about 900 days, stored in phosphate-buffer saline (pH 7.4) in complete absence of magnesium ions. The reported half-life is predicted to be diminished to just five days, if the product is exposed to temperatures of 37 °C [ 3 ]. Another factor determining stability, is RNA length which is calculated to be inversely correlated with stability against hydrolysis [ 3 ].…”
Section: Mrna Stability and Modificationsmentioning
confidence: 99%
“…The reported half-life is predicted to be diminished to just five days, if the product is exposed to temperatures of 37 °C [ 3 ]. Another factor determining stability, is RNA length which is calculated to be inversely correlated with stability against hydrolysis [ 3 ]. Attempts at fortification of mRNA stability employing lipid pharmacotechnic formulations are to be considered carefully: utilization of lipids whose cationic head group can lower the pKa of the 2-hydroxyl group residing on the ribose moiety of the mRNA are best avoided since even a 2-unit shift can significantly hasten mRNA hydrolysis [ 185 , 186 ].…”
Section: Mrna Stability and Modificationsmentioning
confidence: 99%
See 1 more Smart Citation